Explicit and implicit approach vs. avoidance tendencies towards high vs. low calorie food cues in patients with anorexia nervosa and healthy controls. (1st December 2016) - Paslakis, Georgios; Kühn, Simone; Schaubschläger, Anke; Schieber, Katharina; Röder, Kathrin; Rauh, Elisabeth; Erim, Yesim
Abstract: Patients with anorexia nervosa (AN) have a strong ability to limit food intake. Thus, dysfunctional approach vs. avoidance behaviors towards food are evident in AN. We applied an approach-avoidance task (AAT), in which n = 41 AN patients and n = 42 controls either approached ("pull") or avoided ("push") high (HC) vs. low calorie (LC) food pictures based solely on the presented picture format (landscape vs. portrait). We tested the hypothesis that -in opposition to controls displaying an approach bias towards HC food cues- AN patients would show an avoidance bias (measured as different response times) towards HC food. Explicit ratings of food cues were also performed. We found a significant interaction "group" x "direction" (p = 0.03). rm-ANOVAs performed for each of the two groups separately showed a main effect for "direction" of motion in controls (p = 0.02), but not in AN patients (p = 0.40). The two groups did not differ in their reaction times (RTs) with regard to "push" (p = 0.27). However, RTs with regard to "pull" were significantly different between the groups (p = 0.04). Controls show a clear approach bias, expressed by significantly faster RTs for "pull" compared to "push", independent of "calorie" content of the food stimuli. This approach bias is absent in the group of AN patients. This is indicative of a global loss of incentive value of food in AN. Implicit trainings as add-on to psychotherapy in AN patients are asked for.